FOXO3-mediated chemo-protection in high-stage neuroblastoma depends on wild-type TP53 and SESN3 - Rupp, M (Oncogene, 2017)
Forkhead box O class transcription factors are homeostasis regulators that control cell death, longevity and therapy-resistance. In neuroblastoma (NB), nuclear FOXO3 correlates with stage M disease and poor prognosis. To analyze whether FOXO3 contributes to drug-resistance in this childhood cancer, we investigated how different high-stage-derived NB cells respond to the activation of an ectopic FOXO3 allele. We found endogenous FOXO3 mostly localized to the nucleus—upon activation of an ectopic, 4OHT-activated FOXO3(A3)ER fusion protein two of the cell lines underwent apoptosis, whereas in the others FOXO3-activation even increased survival during drug-treatment. In the latter cell type, FOXO3 did not induce the BH3-only protein BCL2L11/BIM due to impaired binding of FOXO3 to the BIM-promoter, but still activated other FOXO3 targets. It was shown before that FOXO3 and TP53 physically interact with each other at two different regions—the TP53-N-terminus binds to the FOXO3-DNA binding domain (DBD) and the FOXO3-C-terminus interacts with the TP53-DBD. Interestingly, cell lines that undergo FOXO3-induced cell death carry homozygous point mutations in the TP53-DBD near the structural hotspot-mutation-site R175H, which abrogated FOXO3–TP53 interaction. In contrast, in FOXO3-death-resistant cells no point mutations in the TP53-DBD were found—in these cells FOXO3–TP53 complexes are formed and FOXO3-binding to the BIM-promoter, but not the induction of the detoxifying protein SESN3, were prevented, which in turn increased chemo-protection in this type of high-stage-derived NB cells. Our combined data suggest that FOXO3 steps in as a death inducer in case of TP53-mutation, whereas functional TP53 alters FOXO3-target-promoter-recognition, which prevents death induction by FOXO3 and instead increases chemo-protection and survival of NB cells. This novel mechanism may explain the low incidence of TP53 mutation in high-stage NB at diagnosis and suggests FOXO3 as a therapeutic target for this childhood malignancy.